Período crítico e manejo agroecológico de plantas espontâneas na cultura do quiabeiro com adubos verdes - Santos, Raimundo Nonato Viana (2019)
The research aimed to evaluate the influence of the climatic season on the periods of spontaneous plant interference in the okra crop in organic system and the viability of green manure intercroppered with okra for plant suppression and increased productivity. Thus, two experiments were carried out: (1) matocompetition of spontaneous plants with okra crop in organic system; (2) consortium of green manure with okra to suppress spontaneous plants and increase crop yield. The first experiment was conducted in two climatic stations in an organic system in the Andiroba village in São Luís-MA. The treatments consisted of increasing periods of coexistence or control of spontaneous plants. These were evaluated for density, dry mass and frequency of occurrence, and crop for commercial productivity. The main spontaneous plants were Commelina benghalensis, Cynodon dactylon, Eleusine indica, Alternanthera tenella and Amaranthus spinosus. The critical period of weed interference in the rainy season was 12 to 36 days after crop emergence and in the dry season, from 04 to 53 days after transplantation. The climatic season influences with less intensity the critical period of interference of spontaneous plants in the okra tree in organic system. The second experiment was carried out at the Jardim São Cristóvão Production Pole in São Luís - MA. The treatments consisted of the green manure Vigna unguiculata, Crotalaria juncea, Mucuna nivea and Cajanus cajan in consortium with okra and in monoculture; besides witnesses without green fertilizers (okra weeding and okra with spontaneous plants). Spontaneous plants were evaluated for dry mass accumulation, phytosociological parameters, species richness, Shannon-Wiener index. The green manure were evaluated for fresh mass, dry mass and vegetal cover; and the crop for the average fruit yield and the equivalent area index. The absence of spontaneous plant management in the okra crop causes high production losses and the green manure, Vigna unguiculata, Crotalaria juncea and Mucuna nivea reduce the negative effects of these species on the crop and present viability agronomic for okra consortia. The rainy season provides greater infestation of spontaneous plants in the okra crop in organic system, but it is in the dry season that the critical period of interference of spontaneous plants is prolonged and yield losses are greater. The green manure in the okra crop reduce the richness of spontaneous species of the botanical group of eudicotyledons and the accumulation of dry mass of the infesting community. The okra consortium with the green fertilizers, Crotalaria juncea, Mucuna nivea and Vigna unguiculata promote greater utilization of the cultivated area and agronomic viability.